Genetic Diversity Analysis of Growth Differentiation Factor 9 (GDF-9) Exon 1 in Boerka Goats via PCR-RFLP - Zarra Naomi Angel; Maskur Maskur; Muhammad Muhsinin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
This study aims to identify polymorphisms in the Growth Differentiation Factor-9 (GDF-9) gene in Boerka goats using the PCR-RFLP method. A total of 60 blood samples were used for DNA isolation. Amplification of the GDF-9 gene Exon 1 produced a 462 bp fragment. Genetic diversity analysis using the HhaI restriction enzyme revealed three genotypes: GG (462 bp), GA (462, 410, and 52 bp), and AA (410 and 52 bp). The frequency of the G allele (0.925) was found to be higher than the A allele (0.075), with a dominant GG genotype frequency of 0.867. The Polymorphic Information Content (PIC) value was 0.129, indicating a low level of genetic diversity in the studied population. Descriptive analysis showed that the heterozygous GA genotype tended to have a higher average litter size than the homozygous genotypes. These results indicate that the GDF-9 gene is polymorphic in Boerka goats and has the potential to be used as a molecular marker in breeding programs.